2005
DOI: 10.1128/mcb.25.9.3639-3647.2005
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Tgif, the Mouse Ortholog of a Human Holoprosencephaly Gene, Does Not Result in Holoprosencephaly in Mice

Abstract: 5-TG-3-interacting factor or transforming growth factor beta (TGF-␤)-induced factor (TGIF) belongs to a family of evolutionarily conserved proteins that are characterized by an atypical three-amino-acid loop extension homeodomain. In vitro studies have implicated TGIF as a transcriptional repressor and corepressor in retinoid and TGF-␤ signaling pathways that regulate several important biological processes. Heterozygous nonsense and missense mutations of the human TGIF gene have been associated with holoprosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 51 publications
(51 reference statements)
8
84
0
Order By: Relevance
“…Moreover, Tgif Ϫ/Ϫ mutant mice are viable and can be bred normally. Our result is consistent with a recent report by Shen and Walsh (2005). This result is strikingly different from the human study, which revealed that loss of Tgif function is associated with human HPE, a typical ventral forebrain malformation (Gripp et al, 2000).…”
Section: Tgif ؊/؊ Embryos Show Normal Brain and Spinal Cord Patterningsupporting
confidence: 82%
See 2 more Smart Citations
“…Moreover, Tgif Ϫ/Ϫ mutant mice are viable and can be bred normally. Our result is consistent with a recent report by Shen and Walsh (2005). This result is strikingly different from the human study, which revealed that loss of Tgif function is associated with human HPE, a typical ventral forebrain malformation (Gripp et al, 2000).…”
Section: Tgif ؊/؊ Embryos Show Normal Brain and Spinal Cord Patterningsupporting
confidence: 82%
“…Since the expression after day 12.5 d.p.c has been reported before (Bertolino et al, 1996;Shen and Walsh, 2005), we focused our Tgif in situ hybridization study on early stages of neural induction and ventral CNS specification during mouse development. We found that Tgif is expressed in the epiblast of the mouse embryo as early as the prestreak stage at day 6.0 d.p.c (E6.0) (Fig.…”
Section: Expression Of Mouse Tgif During Murine Embryonic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments directly assessing the loss of TGIF function will be important for understanding the role of TGIF in human HPE. Of note, the null mutant mouse for Tgif did not show any abnormalities in the structure of the prosencephalon (Shen and Walsh, 2005). It is possible that the Tgif2 gene provides redundancy for Tgif activity in the forebrain.…”
Section: Tgif and Holoprosencephalymentioning
confidence: 93%
“…Studies in Drosophila have indicated that Tgif-related genes are required for normal spermatogenesis (Ayyar et al, 2003;Wang and Mann, 2003). However, the Tgif null mutant mouse did not demonstrate abnormalities in neural development (Shen and Walsh, 2005). Overall, the role of TGIF in vertebrate development is not well understood.…”
Section: Introductionmentioning
confidence: 99%